1978
DOI: 10.1143/jjap.17.1549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impurity Aggregation on the Shift of Thermoluminescence Glow Peak of X-Irradiated KCl: Sr2+

Abstract: A new ultrahigh-resolution photoemission electron microscope called PEEM3 is being developed at the advanced light source (ALS). An electron mirror combined with a sophisticated magnetic beam separator is used to provide simultaneous correction of spherical and chromatic aberrations. Installed on an elliptically polarized undulator beamline, PEEM3 will be operated with very high spatial resolution and high flux to study the composition, structure, electric and magnetic properties of complex materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…For Mn-doped samples Ratnam et a1 (1980) propose that the electron destroys a double hole centre and the resulting single hole recombines with Mn+. Other authors (Ausin and Alvarez-Rivas 1972, Rao and Das 1976, Inabe and Takeuchi 1978, Cases eta1 1982 propose as the mechanism for TL that interstitial halogen atoms are released from traps and recombine with Fcentres; at some stage in this process an electron-hole recombination takes place and gives the observed emission. Rzepka et a1 (1983) have interpreted their results on K1 and KI:Ca2-with this model and have identified the structure of trapped interstitials by means of Raman spectroscopy as polyiodide ions (I; and I;) and I2 aggregates in pure KI, and as H,-type defects or D, centres in KI:Ca2+.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For Mn-doped samples Ratnam et a1 (1980) propose that the electron destroys a double hole centre and the resulting single hole recombines with Mn+. Other authors (Ausin and Alvarez-Rivas 1972, Rao and Das 1976, Inabe and Takeuchi 1978, Cases eta1 1982 propose as the mechanism for TL that interstitial halogen atoms are released from traps and recombine with Fcentres; at some stage in this process an electron-hole recombination takes place and gives the observed emission. Rzepka et a1 (1983) have interpreted their results on K1 and KI:Ca2-with this model and have identified the structure of trapped interstitials by means of Raman spectroscopy as polyiodide ions (I; and I;) and I2 aggregates in pure KI, and as H,-type defects or D, centres in KI:Ca2+.…”
Section: Introductionmentioning
confidence: 96%
“…Very briefly, one can summarise their influence as follows: (i) the presence of divalent impurities in the crystal enhances the total light output Mukherjee 1982, Bhan andRao 1982); (ii) the light emission 'moves' towards low temperature in doped samples, i.e. the low temperature glow peaks are more intense in the intentionally doped samples than in the pure ones (Katz et a1 1972, Damm and Opyrchal 1975, Sharon er a1 1981, Sastry and Balasubramanyam 1978; (iii) the aggregation state of the impurities strongly influences the relative intensity of the glow peaks (Dryden and Shuter 1973, Inabe and Takeuchi 1978, Lopez er a1 1977, Mukherjee 1978. Also in some cases where the impurity changes itsvalence state during irradiation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The first stage peak at 135 C observed in pure KC1 was not observable in doped crystals, down to doses of 135 R. In some studies, on the other hand, the first stage peak at 135C was reported at doses higher than this. The corresponding Z~ centre peak is also at lower temperatures (80-90 C) (Katz et al 1972;Inabe and Takeuchi 1978;Sinha et al 1979). The diverse results, most probably, arise due to the fact that the coloration stage II begins at different doses depending upon impurity concentration, dose rates, etc.…”
Section: Kcimentioning
confidence: 99%
“…The results are summarised in table 2. Some results on other impurities (Inabe et al 1974;Inabe and Takeuchi 1978;Mukherjee 1978;Gartia et al 1980;Sridaran et al 1981;Ratnam 1981, 1982) are also included for comparison. For other impurities also one obtains the 185C peak and the ll0C impurity peak, or in some cases the 135 C peak and the 80C impurity peak.…”
Section: Kcimentioning
confidence: 99%